تجديد النحو فى تعليم اللغة العربية عند إبراهيم مصطفى - muhammad zikri (UIN Fatmawati Sukarno Bengkulu, 2019)
AbstractThe existence of Nahwu's knowledge among other disciplines-Kalam Science, Fiqh, Tasawuf, Tafsir, and Hadith-is one of the traditional knowledge of Arabic (al-'um an-naqliyyah) which still has a significant contribution in Islamic studies. Ibn Khaldun in his al-Muqaddimah viewed the nahwu knowledge as an integral part that can not be separated in the progress of traditional sciences (al-'umul an-naqliyyah), because of the success and truth of the study of the origin of the sciences (al-'ulum an- naqliyyah). The Middle East with a wealth of knowledge and knowledge, especially in linguistics, has produced many thinkers and linguists, especially in the development of Arabic language science. Introducing the figure of a linguist reformist in the modern era, Ibrahim Musthafa.